Ways to Promote the Classroom Participation of International Students by Understanding the Silence of Japanese University Students - Kim, Soonhyang; Ates, Burcu; Grigsby, Yurimi; Kraker, Stefani; Micek, Timothy A. (Journal of International Students, 2016)
The authors explored the role of silence and deciphered its meaning and usefulness as a teaching and learning strategy for Japanese students through a survey of Japanese university students in their home country. This study has revealed that participant responses were evenly divided among comfortable with silence, uncomfortable with silence, and dependent on familiarity with the person. The use of silence by Japanese students varies on a highly individualized basis, not only by culture. The interlocutor is the significant factor, not the topic of conversation, for their comfort with silence. This study also suggests that silence can be used in addition to verbal participation as a form of engaged learning and active participation.